Comparison on abrasive wear of SiCrFe, CrFeC and Al2O3 reinforced Al2024 MMCs - Yilmaz, Serdar Osman (Elsevier Sci Ltd, 2007)
The effects of volume fraction and size of SiCrFe, CrFeC, and Al2O3 particulates on the abrasive wear rate of compo-casted Al2O24 metal matrix composites (MMCs) were studied. The process variables like the stirring speed, position and the diameter of the stirrer have affected the diffusion between particulates and matrix. The abrasive wear rate was decreased by the increase in particulate volume fraction of SiCrFe and CrFeC intermetallic reinforced composites over 80 grade SiC abrasive paper. The wear rates of the all composites decreased with aging treatment, and the best result was seen for the composite having a hybrite structure as SiCrFe and CrFeC particulates together. Nevertheless, the fabrication of composites containing soft particles as copper favors a reduction in the friction coefficient. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: metal matrix composites (MMCs); wear; Al2024